Description Data Completeness in Maternal & Child Health (MCH) Handbook in Temanggung Regency - Yudhy Dharmawan (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2019)
Background: Maternal mortality rate in Central Java in 2015 was still high, at 111 / 100,000 live births. Therefore developed a method for early detection of the cause of death in “Desa Siaga“ Program. In this program include a community-based surveillance. Sources of primary data recording surveillance activities are MCH handbook. Therefore it needs to know how the completeness of MCH handbook as a basis for the development of surveillance system in the villageMethod: Data collection techniques using observations with the checklist instrument to describe data completeness MCH handbook. Population study is MCH handbook what owned by Mothers who have children under five. Samples were MCH handbook in 31 villages with category Active “ Desa Siaga” in the working area three health centers in the district of Temanggung.Results: The average of data completeness in MCH Handbook was 45.29%. For 13 MCH Handbook section was observed, there are only 3 parts completeness above 50%, Ten other parts percentage is less than 50%. Conclusion: There are many data that useful for screening high risk pregnant woman and nutrition growth are incomplete. Incomplete data in MCH Data shown that data is not be urgent in MCH Services. Data in MCH Handbook couldn’t be database for MCH Surveillance in “Desa Siaga “ Program